Garcinia brasiliensis Leaves Extracts Inhibit the Development of Ascitic and Solid Ehrlich Tumors - Silva, Lucas Sylvestre; Cavallini, Eduardo; da Silva, Rafael André [UNESP]; Sant’Ana, Monielle; Yoshikawa, Ariane Harumi; Salomão, Thiago; Huang, Bianca; Craice, Paula; de Souza Ferreira, Luiz Philipe; Della Matta, Heitor Pedro; Gil, Cristiane Damas [UNESP]; Pereira, Maria de Lourdes Gomes; et al. (MDPI, 2025)
Background: Garcinia brasiliensis is traditionally known for its medicinal properties. Objectives: Here, we investigated the effects of crude extract (CE) and ethyl acetate fraction (EAF) obtained from G. brasiliensis leaves on the ascitic (EA) and solid (ES) forms of Ehrlich tumors. Methods: Induced and uninduced BALB/c mice were treated intramuscularly, for 7 or 14 days, with saline solution or CE and EAF, both at a 10% concentration, based on in vitro cytotoxicity assessment. Biochemical analyses were also performed to evaluate in vivo cytotoxicity. In relation to tumor-induced animals, morphological changes, plasma enzymes, inflammatory mediators and the induction of apoptosis were analyzed, in addition to histopathological studies, to evaluate the inhibition of tumor growth. Results: Alanine aminotransferase (ALT), aspartate aminotransferase (AST) and gamma glutamyl transferase (GGT) were regulated by CE and EAF administration. Furthermore, both treatments were effective in inhibiting tumor growth in EA and ES by modulating the levels of interleukin (IL)-6 and tumor necrosis factor (TNF)-α, decreasing mast cells numbers and inducing apoptosis. Conclusions: This research indicates that both CE and EAF from G. brasiliensis leaves have potential antitumor effects with low cytotoxicity.
Keywords: antioxidant; antitumor; Ehrlich tumor; Garcinia brasiliensis